Plasma screening for the T790M mutation of EGFR and phase 2 study of osimertinib efficacy in plasma T790M–positive non–small cell lung cancer: West Japan Oncology Group 8815L/LPS study. Issue 9 (5th February 2020) - Takahama, Takayuki; Azuma, Koichi; Shimokawa, Mototsugu; Takeda, Masayuki; Ishii, Hidenobu; Kato, Terufumi; Saito, Haruhiro; Daga, Haruko; Tsuboguchi, Yuko; Okamoto, Isamu; Otsubo, Kohei; Akamatsu, Hiroaki; et al.
Abstract : Background: Liquid biopsy allows the identification of patients whose tumors harbor specific mutations in a minimally invasive manner. No prospective data have been available for the efficacy of osimertinib in patients with non–small cell lung cancer (NSCLC) who develop resistance to first‐ or second‐generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) and who test positive for the TKI resistance–conferring T790M mutation of EGFR by liquid biopsy. Therefore, a phase 2 study was conducted to assess the efficacy and safety of osimertinib in such patients. Methods: Eligible patients had advanced or recurrent NSCLC with known TKI‐sensitizing mutations of EGFR, had documented disease progression after treatment with at least 1 first‐ or second‐generation EGFR TKI, and were positive for the T790M mutation in plasma according to the Cobas EGFR Mutation Test v2 (Roche Diagnostics) or droplet digital polymerase chain reaction analysis. Patients were treated with osimertinib (80 mg/d) until disease progression. The primary endpoint was the overall response rate (ORR) in patients positive for T790M in plasma by the Cobas assay. Results: Between June 2016 and November 2017, 276 patients were screened for their T790M status with a liquid biopsy. Seventy‐four patients were positive for T790M in plasma, and 53 of these individuals were enrolled in the study. The ORR for evaluable patients positive for T790M in plasma by the Cobas assay (n = 49) was 55.1% (95% confidence interval [CI], 40.2%‐69.3%). The median progression‐free survival for all evaluable patients (n = 52) was 8.3 months (95% CI, 6.9‐12.6 months). Conclusions: The results demonstrate the utility of liquid biopsy for the detection of T790M with the Cobas EGFR Mutation Test v2. Plasma genotyping with this assay is informative for treatment selection in clinical practice when tumor sampling is not feasible. Abstract : The efficacy of systemic treatment with an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor based on the results of liquid biopsy is not well clarified. Results from plasma screening for EGFR T790M with the Cobas EGFR test and digital droplet polymerase chain reaction surrogate the efficacy of systemic treatment with osimertinib in the study.